Analysis of diet-related stroke disease burden in China from 1990 to 2021 and projections for 2025–2044 - Wang, Zhe; Pei, Wenjuan; Gou, Meili; Gao, Chen (Frontiers in Nutrition, 2025)
ObjectiveTo analyze the burden of diet-related stroke diseases in China from 1990 to 2021 and to predict its trends in the next 20 years.MethodExtract data from the 2021 Global Burden of Disease Database and analyze the burden of diet-related stroke d isease in China from 1990 to 2021. And using a time series model to predict the burden of diet related stroke disease in the next 20 years.ResultsIn 2021, the crude mortality rate of diet related stroke in China was 30.70/100,000, and the crude Disability Adjusted of Life Years (DALY) rate was 729.10/100,000. The standardized mortality rate of 21.59/100,000 and the standardized DALY rate of 485.83/100,000 in 2021 have decreased by 54.48 and 55.05%, respectively compared to 1990, but are higher than the levels of high Socio-demographic Index (SDI) regions worldwide. In 2021, the male attributable mortality rate and DALY rate were higher than those of females (39.39/100,000 vs. 21.59/100,000, 942.76/100,000 vs. 505.15/100,000), and the male and female attributable disease burden indicators showed a downward trend over time. In 2021, the mortality rate and DALY rate of diet related stroke were positively correlated with age. Compared to other types of stroke, ischemic stroke has the highest disease burden, and high salt still ranks first among various unhealthy dietary risk factors. Autoregressive Integrated Moving Average (ARIMA) model predicts that the burden of diet related stroke disease will significantly decrease in the next 20 years.ConclusionFrom 1990 to 2021, the burden of diet-related stroke diseases in China has shown a downward trend, and the disease burden problem is more prominent in the older adult population and men. A series of effective measures should be taken to strengthen the healthy diet of key populations. In the next 20 years, the burden of diet-related stroke diseases will significantly decrease.